The Role of Perceived Supervision, Organizational Support and Co-Workers Support to Discourage Knowledge Hiding in Organizations - Walsh, Isabelle; Dalmasso, Audrey; Anand, Amitabh (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
In past literature, the variables that may discourage knowledge hiding in organizations have attracted less attention than the variables that actually cause it. We develop a construct: “Positively Perceived Supervision”. The more supervision is positively perceived, the less employees are inclined to hide their knowledge from their supervisors and from their co-workers. The more employees perceive support from co-workers, the less they will be inclined to hide knowledge from them. Surprisingly, the more employees perceive support from their organization, the more they will be inclined to hide knowledge from their supervisor and co-workers. This leads to managerial implications.